A transparência dos bancos centrais e a efetividde da política monetária - Simão Filho, José (2008)
This paper makes a theoretical analysis of the impact of central bank transparency on the effectiveness of the monetary policy. For this analysis, an evaluation is made to determine if it implies a lower interest rate. Furthermore, the consequences of transparency on accountability, central bank credibility, inflation average, and output gap are considered. The findings denote that central bank transparency improves the conduction of the monetary policy contributing to a decrease in inflation rate and interest rate. As inflation, unemployment and interest rates are determinants of the level of poverty, the central bank s behavior is relevant in its reduction. In this sense, this work reveals a connection between economic transparency and poverty. The theoretical model and ordinary least squared results highlighted that central banks with greater transparency contribute to an improvement in the reduction of income inequality and poverty. Besides, this work makes an analysis concerning the effect of central bank of brazil transparency on macroeconomic variables. With this objective an analysis which takes into consideration the effect caused by announcements and publications of the central bank on several variables related to the inflation targeting system (including expectations) is carried out. The findings denote that the cbb transparency together with an increase in the information quality (clarity) implies a significant change in the rate of readjustment of market expectations. Furthermore, the central bank transparency contributes to anchor the public expectations and to affect long run interest rates.